Differentially regulated high‐affinity iron assimilation systems support growth of the various cell types in the dimorphic pathogen Talaromyces marneffei. Issue 4 (23rd September 2016) - Pasricha, Shivani; Schafferer, Lukas; Lindner, Herbert; Joanne Boyce, Kylie; Haas, Hubertus; Andrianopoulos, Alex
Summary: Iron is a key trace element important for many biochemical processes and its availability varies with the environment. For human pathogenic fungi iron acquisition can be particularly problematical because host cells sequester free iron as part of the acute‐phase response to infection. Fungi rely on high‐affinity iron uptake systems, such as reductive iron assimilation (RIA) and siderophore‐mediated iron uptake (non‐RIA). These have been extensively studied in pathogenic fungi that exist outside of host cells, but much less is known for intracellular fungal pathogens. Talaromyces marneffei is a dimorphic fungal pathogen endemic to Southeast Asia. In the host T. marneffei resides within macrophages where it grows as a fission yeast. T. marneffei has genes of both iron assimilation systems as well as a paralogue of the siderophore biosynthetic gene sidA, designated sidX . Unlike other fungi, deletion of sidA or sidX resulted in cell type‐specific effects. Mutant analysis showed that T. marneffei yeast cells also employ RIA for iron acquisition, providing an additional system in this cell type that differs substantially from hyphal cells. These data illustrate the specialized iron acquisition systems used by the different cell types of a dimorphic fungal pathogen and highlight the complexity in siderophore‐biosynthetic pathways amongst fungi. Abstract : The opportunistic fungal pathogen Talaromyces marneffei (formerly known as Penicillium marneffei ) is endemic to Southeast Asia and represents an important and escalating health threat to immunocompromised individuals. T. marneffei undergoes a thermally dependent morphological switch from non‐pathogenic hyphal cells at 25°C to pathogenic yeast cells at 37°C. The ability of pathogenic fungi to proliferate within the host is dictated by strategic acquisition of nutrients, such as iron. Two iron‐uptake mechanisms have been identified in fungi for the acquisition of iron under low iron conditions, these include the reductive and non‐reductive iron assimilation systems. Restricting the ability of fungi to acquire iron through these systems has been shown to reduce virulence and is a possible avenue for disease control. In this study, we show that T. marneffei yeast cells rely on both iron uptake systems, highlighting a key difference between hyphal and yeast cell types, and this may be an explanation for their success within host cells as they may scavenge iron more effectively. In addition we identified the presence of a duplicated non‐reductive iron assimilation gene, relatively uncommon amongst other fungi. Deletion of this gene resulted in severe growth defects under low iron conditions and presents itself as a good target for antifungal drugs.